Evaluación de la eficacia de métodos de remoción de caries químico-mecánico en niños: revisión bibliográfica - Bonilla Gavilanes, Víctor Alejandro (2025)
Introduction: The loss of dental organs due to extensive curing processes can lead to changes at functional, aesthetic and psychosocial levels. The basis of treatment has been and continues to be the mechanical removal of caries using high or low speed rotating instruments, which can cause anxiety in children, so in recent years chemomechanical caries removal (CMCR) has begun to be used. Objective: To evaluate the efficacy of the chemical-mechanical methods Brix 3000, Papacarie and Carisolv in the removal of caries in children through a literature review, and thus obtain useful information about these procedures. Method: A qualitative, relational and descriptive bibliographic review, using the PubMed, Wiley and LILACS databases as a source of information, in which scientific articles related to the subject of the study were searched for using search strings and inclusion criteria. Results: Initially a total of 67 scientific articles were identified, however, after a process of discarding and selection only 12 were chosen as valid for the research. Conclusions: On evaluating the efficacy of the chemical-mechanical methods Brix 3000, Papacarie and Carisolv in the removal of caries in children, it was determined that all three methods are effective in the removal of carious tissue, as they can reach tiny spaces in the tooth and only eliminate the carious tissue without affecting the healthy structure of the tooth, so their use is recommended as an alternative treatment to the conventional method.